Fun and Games: The Suppression of Architectural Authoriality and the Rise of the Reader - Elizabeth Keslacy (Footprint)
Between the Roarkian caricature of the heroic modernist and the spectre of the contemporary starchitect, there was a period of resistance in which architectural authoriality came under fire. One of the most explicit challenges was issued through the use of gaming and simulation in both architectural education and practice in the 1960s and the 1970s, particularly in the work of Juan Pablo Bonta and Henry Sanoff - both of them architectural scholars, educators, and game enthusiasts.  By tracing the importation of gaming and simulation techniques into architecture, this paper will show how architectural games sought to refigure the architect as a collaborative figure embedded in a network of experts, participants and constituents, and to modulate the architect’s design authority by foregrounding the contributions of viewer-interpreters to the creation of meaning. Situating their work within gaming precedents, from war and business games to urban planning gaming-simulations, I show how architecture games - particularly design games - worked to develop the architectural reader as a creative force, in some quarters going so far as to posit interpretation as the basis of design.